2021
DOI: 10.47829/ajsccr.2021.3801
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study On the Prevalence of Road Traffic Accident and Associated Risk Factors Among Drivers in Bauchi State, Nigeria

Abstract: 1.1. Background: Worldwide Road traffic accident (RTA) is a huge public health and development problems killing nearly 1.2 million people a year and injuring or disabling between 20-50 million people worldwide; thus making the loss of US 518 billion dollars globally. According to World Health Organization, every day more than 3000 people die from road traffic accidents. Developing countries account for 90% of global road traffic deaths. Road traffic accidents are being the critical public health problem that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…Previous studies addressed the prevalence of RTA among victims through a retrospective study design, which could not give significant information to decision-makers due to the design itself ( 45 ). In addition, pieces of evidence from quantitative studies revealed the prevalence of RTA ( 23 , 28 , 31 , 33–36 , 40 , 46 ); in Ethiopia, particularly in the study area, there is a paucity of information regarding the contributing factors among drivers of public transportation to the occurrence of traffic accidents on the roads and public health concerns. Moreover, little was known about the prevalence of traffic accidents on the roads and the contributing factors among drivers of public transportation with a community-based cross-sectional study design.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies addressed the prevalence of RTA among victims through a retrospective study design, which could not give significant information to decision-makers due to the design itself ( 45 ). In addition, pieces of evidence from quantitative studies revealed the prevalence of RTA ( 23 , 28 , 31 , 33–36 , 40 , 46 ); in Ethiopia, particularly in the study area, there is a paucity of information regarding the contributing factors among drivers of public transportation to the occurrence of traffic accidents on the roads and public health concerns. Moreover, little was known about the prevalence of traffic accidents on the roads and the contributing factors among drivers of public transportation with a community-based cross-sectional study design.…”
Section: Introductionmentioning
confidence: 99%
“…According to a systematic research by Khatib et al, the frequency of traffic accidents resulting in injury or death varied between 11.1 and 42.6% for individuals in the 20–30 age group and between 4.6 and 97.2% for male subjects ( 22 ). Furthermore, a study conducted in Nigeria (38.3 and 35.3%) ( 23 , 24 ), Vietnam (20%) ( 25 ), and Saudi Arabia (63%) ( 26 ) revealed the prevalence of RTA. Furthermore, in the national context, different studies have revealed repeated occurrences of RTA with different magnitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…75% of road traffic deaths came about because vehicles collided with each other in low-earning income countries despite owning only 32% of yearly fatalities for every 10,000 cars around the world, making this claim unbelievable. Globally, an estimated cost of US$ 518 billion is spent on RTAs [36] . The share of the developing countries is about US $100 billion, representing 1 to 3 per cent of their gross national product [37] .…”
Section: Introductionmentioning
confidence: 99%
“…According to a survey conducted in 204 countries, it has been found that 1.1 to 1.3 billion people smoke globally. The smoking addiction rate is very high and smoking cessation and preventive programs are not greatly effective 11 . Studies have revealed that cigarette smoking directly and indirectly impaired bone mineral density.…”
Section: Introductionmentioning
confidence: 99%